SISTEM PAKAR UNTUK MENDIAGNOSIS HAMA DAN PENYAKIT TANAMAN PISANG DENGAN TEOREMA BAYES - Lievia Anjhelina Maharani; Gibtha Fitri Laxmi; Freza Riana (Jurnal Ilmiah Teknologi Infomasi Terapan, 2021)
Tanaman pisang merupakan salah satu tanaman yang banyak dijumpai di daerah-daerah di Indonesia, padahal di Indonesia sendiri masih minim informasi yang diterima masyarakat tentang hama dan penyakit yang dapat menyerang tanaman pisang dan cara penanggulangannya. Terbatasnya ketersediaan tenaga ahli di berbagai tempat atau wilayah diIndonesia causes the community to be late in dealing with pests and diseases of banana plants, therefore this research creates a website-based expert system to diagnose pests and diseases of banana plants using 11 data consisting of 5 pests and 6 diseases, as well as 48 symptom data that will be processed using the Bayes Theorem method to produce a probability value of a pest or disease based on the symptoms that arise in banana plants. This study resulted in an accuracy value of 86.53%. The accuracy value is obtained from the comparison between expert diagnosis and the system using the Bayes theorem based on 52 tested data. This expert system can help the community in diagnosing banana plant pests and diseases.